Association of sport participation in preterm and full term born children and body and fat mass indices from age 3 to 14 years. Issue 5 (May 2020) - Spiegler, Juliane; Mendonça, Marina; Wolke, Dieter
Abstract: Objectives: To assess the association of gestational age groups (VP: <32 weeks, MP: 32–33 weeks, LP: 34–36 weeks and FT: ≥37 weeks of gestation) and club sport participation in childhood on body mass index (BMI), fat free mass index (FFMI) and fat mass index (FMI). Design: Longitudinal, cross sectional. Methods: BMI (age 3, 5, 7, 11 and 14 years; N = 10581–14702) and FFMI/FMI (age 7, 11 and 14 years; N = 10446–12996) and consistent club sport participation at age 5, 7 and 11 years (ranging from never participating to participating at all three ages) were assessed prospectively. These were compared by gestational age and their associations with BMI and FMI were investigated, while controlling for confounders (socio-economic, maternal obesity, child related, diet). Results: BMI and FFMI was lower in VP or MP until age 7, but no differences were found in BMI, FFMI or FMI after age 11 with regard to gestational age. Consistent club sport participation from age 5–11 was unrelated to BMI at ages 3–7. However, FT children with club sport participation had lower BMI and FMI at ages 11 and 14; but this association was not found in VP or MP. Conclusions: During adolescence body composition of VP and MP become similar to FT born peers. Consistent sport participation reduces BMI and FMI in FT only. In VP or MP children modifying effects of sport on body composition might not be detected due to the catch-up growth in weight, height and fat mass at the same time.